Efficient Direct Cytosolic Protein Delivery via Protein-Linker Co-engineering - Wei, Lixia; Wang, Heyun; Özkan, Melis; Damian-Buda, Andrada-Ioana; Loynachan, Colleen N.; Liao, Suiyang; Stellacci, Francesco (ACS Applied Materials and Interfaces, 2025)
Protein therapeutics have enormous potential for transforming the treatment of intracellular cell disorders, such as genetic disorders and cancers. Due to proteins’ cell-membrane impermeability, protein-based drugs against intracellular targets require efficient cytosolic delivery strategies; however, none of the current approaches are optimal. Here, we present a simple approach to render proteins membrane-permeable. We use arginine-mimicking ligand N,N′-dimethyl-1,3-propanediamine (DMPA) to functionalize the surface of a few representative proteins, varying in isoelectric point and molecular weight. We show that when these proteins have a sufficient number of these ligands on their surface, they acquire the property of penetrating the cell cytosol. Uptake experiments at 37 and 4 °C indicate that one of the penetration pathways is energy independent, with no evidence of pore formation, with inhibition assays indicating the presence of other uptake pathways. Functional tests demonstrate that the modified proteins maintain their main cellular function; specifically, modified ovalbumin (OVA) leads to enhanced antigen presentation and modified cytochrome C (Cyto C) leads to enhanced cell apoptosis. We modified bovine serum albumin (BSA) with ligands featuring different hydrophobicity and end group charges and showed that, to confer cytosolic penetration, the ligands must be cationic and that some hydrophobic content improves the penetration efficiency. This study provides a simple strategy for efficiently delivering proteins directly to the cell cytosol and offers important insights into the design and development of arginine-rich cell-penetrating peptide mimetic small molecules for protein transduction.
CRIS-Team Scopus Importer:2025-05-09
Keywords: arginine-mimicking ligand; cell penetration; cytosolic delivery; membrane permeability; protein functionalization; protein therapeutics